Inadmissibility and remedies - Sharma, Raj (Author of Inadmissibility and remedies); Daghighian, Aris (Immigration law series, 2022)
"This book will be a concise treatment of the process, procedure and strategic elements involved in overcoming claims of inadmissibility related to criminality (both categories of "criminality" and "serious criminality"), medical reasons, or as a result of misrepresentation. A lot of the book will be dedicated to the process and procedure in trying to overcome hurdles, including a special chapter for criminal practitioners called the "Collateral Consequences to Criminality." Remedies, including rehabilitation, humanitarian and compassionate applications, and Ministerial Relief, among others, will be covered at length."--